Textile-based soft robotics for active assistance and rehabilitation - Yılmaz, Ayşe Feyza (Graduate School, 2024)
Recent advancements in the field of robotics have proven that soft robots can be used as wearable supports for neuromuscular disorders due to their compliance and ability to imitate complex motions. Soft pouch motors, engineered to mimic the natural movements of skeletal muscles, play a crucial role in advancing robotics and exoskeleton development. However, fabrication techniques often involve multi-stage processes; they lack soft sensing capabilities and are sensitive to cutting and damage. Previous research showed that elastomeric, i.e. silicone, soft pneumatic actuators have a great potential to create soft-wearable robotic devices for these applications. Nevertheless, it takes time to manufacture these types of actuators due to long preparation times. Although silicone-based materials have favorable properties, such as heat, chemical resistance, and the capacity to conform to different range motions, they do present challenges in terms of material density, stiffness, and strength. This work introduces a new textile-based pouch motors with the capacity for biaxial actuation and capacitive sensory functions, achieved through the application of computerized knitting technology using ultra-high molecular weight polyethylene yarn (Spectra®) and conductive silver yarns. This method enables the rapid and scalable mass fabrication of robust pouch motors. The resulting pouch motors exhibit maximum lifting capacity of 10 kilograms, maximum contraction of 53.3% along the y-axis, and transverse extension of 41.18% along the x-axis at 50 kPa pressure. Finite Element Analysis (FEA) closely matches the experimental data, validating the design and performance of these pouch motors. The capacitance signals in relation to contraction motion are well-suited for detecting air pressure levels and hold promise for applications requiring robotic control. A practical demonstration of the potential of these pouch motors is showcased through the development of a soft ankle exosuit designed to provide lifting support for individuals with foot drop, a condition that impairs the ability to lift the front part of the foot. The exosuit effectively elevates an ankle joint simulator to a 20-degree angle. Moreover, the application of approximately 35 degrees of dorsiflexion torque to a human foot has been successfully achieved under a pressure of 50 kPa, highlighting its potential in assisting with mobility challenges. This study underscores the importance of incorporating both actuation and sensing capabilities in soft robotic systems, which can significantly enhance functionality and user experience. This work not only advances the field of soft robotics but also offers a solution for improving the quality of life for individuals with impaired muscle function. Through the integration of robust, scalable fabrication techniques and advanced materials, this research paves the way for the next generation of assistive devices, promising greater independence and mobility for users. The most challenging aspect of this work was to provide dorsiflexion movement to the foot through a textile-based actuator. Therefore, numerous preliminary studies and methods were attempted to achieve this goal. These preliminary studies evaluated actuators that generated insufficient force for lifting the foot and were applied in exoskeleton-assisted glove applications for the hand. These studies were included in the "Previous Works" section of the thesis. Moreover, healthy individuals naturally perform the gait phases of "heel strike," "stance," "heel off," and "swing" during walking. When the swing phase begins, the ankle dorsiflexes, lifting the toes off the ground to ensure the continuity of the walking cycle, which starts with the heel strike. During the preliminary studies, a novel interdigital capacitive textile sensor was developed using knitting technology to analyze gait through human knee movements. The details of this study are included in the "Previous Works" section. However, controlling the robotic system using this sensor proved to be complex. Therefore, a simpler method was implemented: a textile-based presence/absence sensor placed on the heel. This approach simplified the control system, making it more manageable.
Aktif destek ve rehabilitasyon için tekstil tabanlı yumuşak robotikler
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2024
Keywords: soft robotics; yumuşak robotikler